2012
DOI: 10.1007/s00167-012-2105-4
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve of office-based ultrasonography for rotator cuff tendons tears

Abstract: Diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…This reproducibility is also supported by other series [6] and evaluated in recent studies such as in Seijas et al [7] . Studies on interobserver variability with ultrasound in tendons have shown a very high concordance rate, specifically in knee a very high correlation rate has been shown [8] .…”
Section: International Journal Of Orthopaedicssupporting
confidence: 80%
“…This reproducibility is also supported by other series [6] and evaluated in recent studies such as in Seijas et al [7] . Studies on interobserver variability with ultrasound in tendons have shown a very high concordance rate, specifically in knee a very high correlation rate has been shown [8] .…”
Section: International Journal Of Orthopaedicssupporting
confidence: 80%
“…The learning curve in musculoskeletal US was found to be an important aspect in the time of gaining skills in beginner ultrasonographers [33][34][35]. The 2 beginner members of team B rapidly achieved knowledge about MCP examination.…”
Section: Discussionmentioning
confidence: 99%
“…Other related studies reporting on US evaluations of musculoskeletal conditions by physicians who were previously inexperienced with the use of US have included instruction ranging from 5 hours to 7 days; however, in contrast, we provided only 30 minutes of instruction . This discrepancy may be explained in part by the heterogeneous populations participating in the studies.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, an investigation of the learning curve for US performance by hand surgeons has not previously been explored in the literature. However, there have been some studies that reported on the learning curve for the use of US in evaluations of rotator cuff disorders by orthopedic surgeons who were previously inexperienced with US . Alavekios et al reported on the results of 200 consecutive shoulder US examinations conducted by each of 2 orthopedic surgeons who were previously inexperienced with the use of US and who received 3 days’ worth of instruction at an instructional course.…”
Section: Discussionmentioning
confidence: 99%